THE IMPACT OF NOCTURIA ON MORTALITY : A SYSTEMATIC REVIEW - Jaya Amal, Rizki (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The International Classification of Sleep Disorders (ICS) describes nocturia as "voiding that occurs during the main sleep period". However, there are some medical specialists who do not believe that feeling one emptiness while sleeping qualifies as a clinically important occurrence. They believe that this viewpoint is supported by the evidence. This might be owing to the fact that some studies have indicated that having fewer than two voids every night is not an issue, whilst other studies have found that having more than two voids every night can reduce quality of life. Having fewer than two voids every night is not a problem. Having more than two voids every night is a problem. The most common and bothersome symptom related to urination is called nocturia. 10 million people in the United States suffer with nocturia, yet only 1.5 million get treated for it. This annoys seventy percent of individuals over the age of thirty who get up at least twice throughout the night to use the toilet. People who suffer from the illness known as nocturnal enuresis are characterized by their inability to recognize when they have a full bladder and their involuntary need to empty while sleeping. Nocturia is quite similar to nocturnal frequency, with the exception that sleep comes before and after episodes of urination. Even though voiding diaries call it nocturia, getting up in the middle of the night for any reason other than to urinate is not considered to be nocturia. Convenience void. Nocturia is frequently caused by overactive bladders rather than illnesses of the urinary system. Patients who experienced urine urgency in the afternoon were also likely to have nocturia. Mortality is increased in patients with nocturia who have three or more nocturnal voids per night. The condition known as nocturia has been linked to an increased risk of death. Those who have had nocturia more than three times are at an increased risk of mortality.